(3JaSjQ GdbQBfs - (3GdgcGQj , CMeO Hf CMeO Hf CMeO Hf GdMSjf Hf ehSi, TgGH GdOjf,J (B763 (3g` s
(3ChdgG (B:s
(3jHJOF HJaSjQ bhdg JYGdi (B:- (3QHfG dGJRZ bdhHfG (B" (3ef ShQI Bd YeQGf (B" s
(3BNQgG (B:s
(3hjfJgi HJaSjQ bhdg JYGdi (B:" (3hEP bGd Gddg jG YjSi GHf eQje (B" (3GdBjI ef ShQI GdeGFOI s
(3HgPG GdLRA fbU ai YOI ehGVYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B91 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B145s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B30 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJaSjQ hYdhe GdbQBfs